Lightweight structural composites with electromagnetic applications - Botelho, Edson Cocchieri [UNESP]; Nohara, Evandro Luís; Rezende, Mirabel Cerqueira (Elsevier, 2015)
In the aerospace field, the use of multifunctional composites has become increasingly important in combining different properties within a single component. This chapter addresses the topic of structural polymer composites reinforced with glass, aramid, and carbon fibers impregnated with epoxy resin, specifically their mechanical properties, their susceptibility to hygroscopic environments, and their behavior when impinged with microwaves (8-12. GHz). It is worth mentioning that, many times, it is required that a component reflect microwaves, such as during landing and takeoff procedures in the process of aircraft identification. On the other hand, it is important that the structural composites be microwave-transparent, such as when applied to aircraft and missile radomes. In any situation, it is required that the composite structure attenuates electromagnetic radiation, thereby making a military aircraft, for example, invisible to a radar. Thus, this chapter addresses multifunctional composites and correlates their mechanical behavior with microwave-laminate interaction in the microwave range.
Keywords: Hygrothermal effect; Mechanical properties; Multifunctional composites; Radar cross section; Reflectivity; Thermoset composites